Widely tunable dual-color waveguide-based optical parametric oscillator - Timmerkamp Maximilian; Gao Ming; Fallnich Carsten (EPJ Web of Conferences)
Exploiting four-wave mixing in two orthogonally polarized fundamental modes of Si3N4 waveguides and a tunable birefringence in the cavity, an optical parametric oscillator generates two independently tunable output frequencies from 0 to 62 THz difference.